GREEN ACCOUNTING IMPLEMENTATION AND ENVIRONMENTAL PERFORMANCE ON THE VALUE OF MINING COMPANIES LISTED ON THE IDXYEAR 2020-2023 - Rita JD Atarwaman; Yuyun Yuniarti Layn; Siti H Sangaji (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Background : Raising awareness of the importance of protecting the environment and encouraging sustainable business practices. Objective : This study aims to test the effect of green accounting implementation and environmental performance on company value. Research Method : This research uses a quantitative approach. with technique observation and data analysis . The research sample is a mining company listed on the Indonesia Stock Exchange and participating in the PROPER program of the Ministry of Environment and Forestry of the Republic of Indonesia for the period 2020-2023. Hypothesis testing was carried out using SPSS software and multiple linear regression models. Research Results : The results of this study indicate that green accounting has a positive effect on company value, while environmental performance has no effect. Originality/Novelty of the Research : This research can contribute to additional literature related to research on green accounting and environmental performance in mining companies in Indonesia. This research also re-evaluates green accounting variables that still have different findings in previous studies and are considered relevant to the company's real actions in quantitative evaluation of environmental protection costs and effectiveness. Keywords : Green accounting, Environmental Performance, PROPER Rating, Company Value.